Moral resilience protects nurses from moral distress and moral injury - Galanis, Petros (Nursing ethics, 2025)
Background: The relationship between moral resilience, moral distress, and moral injury among nurses during the COVID-19 pandemic has been widely investigated; however, the literature in the post-COVID-19 era is scarce.Research aim: To examine the impact of moral resilience on moral distress and moral injury among nurses after the COVID-19 pandemic.Research design: Cross-sectional study.Participants and research context: We obtained a convenience sample of 1118 nurses in Greece. We collected demographic data (gender, age) and work-related data (understaffed wards, shift work, clinical experience). We measured moral resilience with the revised “Rushton Moral Resilience Scale”, moral distress with the “Moral Distress Thermometer”, and moral injury with the “Moral Injury Symptom Scale-Healthcare Professionals” version. We adjusted all multivariable models for demographic variables.Ethical considerations: The Ethics Committee of the Faculty of Nursing, National and Kapodistrian University of Athens approved our study protocol (approval number; 474, approved: November 2023). Our study followed the Declaration of Helsinki.Findings/results: Multivariable linear regression analysis showed that moral resilience reduced moral distress and moral injury. In particular, we found that increased response to moral adversity was associated with decreased moral distress (adjusted coefficient beta = −1.81, 95% confidence interval [CI] = −2.07 to −1.54). Moreover, we found that increased response to moral adversity (adjusted coefficient beta = −8.24, 95% CI = −9.37 to −7.10) and increased moral efficacy (adjusted coefficient beta = −3.24, 95% CI = −5.03 to −1.45) were associated with reduced moral injury.Conclusions: Moral resilience can reduce the level of moral distress and moral injury among nurses. However, the persistence of moderate moral resilience among Greek nurses does not guarantee its sustainability. To ensure that this resilience is maintained and potentially enhanced, it is imperative for nurse leaders and policymakers to strategically design interventions to address issues at the organizational, team, and individual levels.